Impact of IPSS-M implementation in real-life clinical practice - Zamanillo, Irene; Poza, Maria; Ayala, Rosa; Rapado, Inmaculada; Martinez-Lopez, Joaquín; Cedena, Maria Teresa (Frontiers in Oncology, 2023)
Objectives The IPSS-M is a recently published score for risk stratification in myelodysplastic syndromes (MDS), based on clinical and molecular data. We aimed to evaluate its relevance on treatment choice in a real-life setting. Methods We retrospectively collected clinical, cytogenetic and molecular data from 166 MDS patients. We calculated IPSS-R and IPSS-M scores and compared Overall Survival (OS) and Leukemia Free Survival (LFS). We also analyzed which patients would have been affected by the re-stratification in terms of clinical management. Results We found that 86.1% of the patients had at least one genetic alteration. The most frequent mutated genes were SF3B1 (25.9%), DNMT3A (16.8%) and ASXL1 (14.4%). IPSS-M re-stratified 48.2% of the patients, of which 16.9% were downgraded and 31.3% were upgraded. IPSS-M improved outcome prediction, with a Harrell’s c-index of 0.680 vs 0.626 for OS and 0.801 vs 0.757 for LFS. In 22.2% of the cohort, the reclassification of the IPSS-M could potentially affect clinical management; 17.4% of the patients would be eligible for treatment intensification and 4.8% for treatment reduction. Conclusions IPSS-M implementation in clinical practice could imply different treatment approaches in a significant number of patients. Our work validates IPSS-M in an external cohort and confirms its applicability in a real-life setting.